A constituição da escola evangélica de Carambeí: uma instituição educacional da imigração holandesa na Região dos Campos Gerais - PR - Cordeiro, Sonia Valdete Aparecida Lima (2006)
On this work, we study the process of creation and installation of the Dutch school in the region of Campos Gerais, during the First Republic, trying to articulate it to the specific objectives, as follows: registering the changes and the main characteristics of this ethnic group when arriving in the country and setting up in the colony in Paraná; analyzing the importance of religion in the formation of the school. To reach these objectives, the study will be structuralized and organized having the theoretician-metodological referential based in the historical materialism. The research has as its object the rescue of the historical process of constitution and institutionalization of the school in the First Republic, period marked by a liberal ideal that considered freedom, gratuitousness, obligation and laity for public instruction. From the point of view of the school Institutions, there aren’t studies that deal with the historical process of school constitution and institutionalization of the Dutch in Brazil. The relevance of this research is justified by the need to understand this initial process of the Dutch school Institutions in the region. A contextualization also becomes necessary, longing to understand the diverse reasons that made the Dutch immigration in this period occur and, specially, to this locality. The methodology considered was survey and catalogation of primary and secondary sources in the School, the “Casa da Memória in Carambeí, a museum dedicated to the city where the museum is” and the one in the city of Ponta Grossa , in the Public Archive of Paraná State, in the Campos Gerais Museum, in the private Archives of descendants of Dutch people, in Documentary Sources: Laws, Decrees, Regulations, Judicial directives, minute Meetings, the School Pedagogical Project , as well as periodicals of the time. In Carambeí, education and religion started with this group of Dutch immigrants.